2023
DOI: 10.1186/s42155-023-00360-3
|View full text |Cite
|
Sign up to set email alerts
|

Embolization for acute nonvariceal bleeding of upper and lower gastrointestinal tract: a systematic review

Abstract: Background Acute non-variceal gastrointestinal bleedings (GIBs) are pathological conditions associated with significant morbidity and mortality. Embolization without angiographic evidence of contrast media extravasation is proposed as an effective procedure in patients with clinical and/or laboratory signs of bleeding. The purpose of this systematic review is to define common clinical practice and clinical and technical outcomes of blind and preventive embolization for upper and lower gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Roberts highlighted a 6.1% complication rate, demonstrating safety in bleeding ruptured VAPs [ 66 ]. Furthermore, the safety results of our report, including vascular access site complications, align with previous studies conducted on endovascular treatments and transcatheter arterial embolization [ 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ]. Finally, this retrospective multicenter study provides further evidence supporting the safety and efficacy of endovascular embolization using EVOH copolymer-based non-adhesive liquid embolic agents (NALEAs) for the management of visceral pseudoaneurysms.…”
Section: Discussionsupporting
confidence: 88%
“…Roberts highlighted a 6.1% complication rate, demonstrating safety in bleeding ruptured VAPs [ 66 ]. Furthermore, the safety results of our report, including vascular access site complications, align with previous studies conducted on endovascular treatments and transcatheter arterial embolization [ 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ]. Finally, this retrospective multicenter study provides further evidence supporting the safety and efficacy of endovascular embolization using EVOH copolymer-based non-adhesive liquid embolic agents (NALEAs) for the management of visceral pseudoaneurysms.…”
Section: Discussionsupporting
confidence: 88%
“…Transcatheter arterial embolization (TAE) is the mainstay of treatment for acute major hemorrhage [ 1 , 2 , 3 ]. A multitude of conditions, including trauma, tumors, iatrogenic injuries, and coagulation disorders, can cause major acute bleeding and may benefit from TAE [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with several previous studies and meta-analyses, our results have confirmed TAE as a valuable therapeutic option for GIB, with high technical and clinical success and a low complication rate[ 33 , 34 ]. More specifically, a high technical success and favourable clinical outcomes were previously reported for TAE procedure in about 80% of patients with detected upper GIB and in lower GIB unresponsive to systemic therapy that cannot be managed in any other way[ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal bleeding (GIB) is a severe and potentially life-threatening condition leading to high mortality and morbidity rates, especially in those patients with delayed treatment or multiple comorbidities[ 1 , 2 ]. Due to the increasing life expectancy and the ever more frequent employment of oral anticoagulant agents, GIB has become a greater health concern in the Western world[ 3 - 5 ].…”
Section: Introductionmentioning
confidence: 99%